Kendala Asas Retroaktif dalam Penanganan Pelanggaran HAM Berat - Syifa Azzohra; Mirza Satria Buana (AHKAM, 2026)
Although the application of the retroactive principle in resolving gross human rights violations has been widely studied, discussions that specifically examine the regulation of the retroactive principle and the juridical obstacles affecting the effectiveness of its application in the Indonesian legal system remain limited. This study aims to analyze the regulation of the retroactive principle in handling gross human rights violations and to examine the legal obstacles affecting its implementation. This study used a normative legal method with statutory and case approaches. The research data, consisting of primary and secondary legal materials, were collected through a literature study of laws and regulations, court decisions, books, and scientific journals, then analyzed descriptively and analytically. The results showed that the application of the retroactive principle to gross human rights violations in Indonesia obtains legitimacy through Law Number 26 of 2000 concerning Human Rights Courts as an exception to the principle of legality to prevent impunity for perpetrators of extraordinary crimes. However, the effectiveness of its application still faces several obstacles, particularly limited institutional capacity, issues of legal politics, and the suboptimal synergy between national and international legal mechanisms. A comparison with Japan shows that the success of enforcing justice is determined not only by the existence of legal norms but also by institutional support and the state’s commitment to human rights enforcement. These findings contribute to the development of human rights law studies, particularly in understanding the relationship between the principle of legality, the retroactive principle, and transitional justice. The implications of this study may serve as a consideration for policymakers in strengthening mechanisms for resolving gross human rights violations and encouraging further research on the effectiveness of integrating national and international legal mechanisms in human rights enforcement.